(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The article deals with the problems of rational legislation, and falls into three parts. The first part embraces terminological data and a very brief discussion of certain shortcomings of the legislative process in Poland. In the second one an attempt has been made to formulate a model of rational legislative process. In the third one some postulates as to how law should be made have been put forward. In order to put into shape a model of a legislative process it is necessary to formulate an exhaustive amount of questions (problems), to be resolved by legislators, and to establish in what sequence they should be resolved. The new suggestions as to the legislative process have been inspired by the shortcomings of the present system of jurisdiction and the imperfections of the present legislative practice. Among the directives related to the legislative process those have been distinguished and discussed which either point to the foundations of the postulated bills and amendments, or specify the conditions behind a rational resolution concerned with the effect of the legislation on public life, finally those which pertain to the choise of legal measures, indicate how to optimize the legislative work and formulate the texts of the provisions of the law. Due mention has also been made of the directives which establish an ideological model of legislation in a socialist state, i.e. pertaining to democratizing the legislative process and the rule of law in the legislative activities of the state.